The Attitude of Patients from a Romanian Tertiary Cardiology Center Regarding Participation in Biomarker-Based Clinical Trials - Iulia Rusu (MDPI AG, 2021)
Background and Objectives: biomarker-based studies are the cornerstone of precision medicine, providing key data for tailored medical care. Enrollment of the planned number of patients is a critical determinant of a successful clinical trial. Moreover, for inclusive medical care, patients from different socio-demographic backgrounds must be recruited. Still, a significant number of trials fail to reach these prerequisites. Designing the informed consent forms based on the patients’ feedback could optimize accrual. We aimed to explore the attitudes of patients from a Romanian tertiary cardiology center towards participation in biomarker-based clinical trials. Materials and Methods: three hundred forty inpatients were interviewed based on a semi-structured questionnaire which included four sections: demographics, personal medical history, attitudes and trust. Results: Roughly, 62.5% of the respondents were interested in enrolling, while altruistic reasons were the most frequently expressed. Clear exposure of the possible risks was most valued (37.78%), followed by the possibility of directly communicating with the research team (23.78%). The most frequently chosen answer by acutely ill patients was improvement of their health, whereas chronically ill individuals indicated the possibility of withdrawal without affecting the quality of medical care. Importantly, the participation rate could be improved if the invitation to enrollment were made by both the current physician and the study coordinator (p = 0.0001). The level of trust in researchers was high in more than 50% of the respondents, and was correlated with therapeutic compliance and with the desire to join a biomarker study. Conclusions: the information gained will facilitate a tailored approach to patient enrollment in future biomarker-based studies in our clinic.